1977
DOI: 10.2136/sssaj1977.03615995004100020036x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Soil Urease Activity and Other Soil Properties

Abstract: Surface samples of 21 diverse Iowa soils representing a wide range in pH, texture, and organic matter content were studied to determine the relationships between soil urease activity and other soil properties.Simple correlation analyses showed that urease activity was correlated very highly significantly with organic C (r = 0.72***), total N (r = 0.71***), and cation‐exchange capacity (r = 0.67***). Urease activity also was significantly correlated with clay (0.53*), sand (−0.47*), and surface area (0.45*), bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1
3

Year Published

1978
1978
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 0 publications
5
36
1
3
Order By: Relevance
“…Die hoer urease-aktiwiteite van die ondergronde as die van die ooreenstemmende bogronde (Tabel 2) is waarskynlik te wyte aan die hoer kleiinhoude daarvan (Tabell). Kleik6110lde is ook in staat om die afbraak van urease te inhibeer (Zantua, Dumenil & Bremner, 1977;Reynolds, Wolf & Armbruster, 1985). In die bogrondebestaan daar vir 'n periode van 10 tot 49 uur na toediening die gevaar dat ureum na di'e ondergronde sall60g (Tabel 2).…”
Section: Result~te En Bespreklngunclassified
“…Die hoer urease-aktiwiteite van die ondergronde as die van die ooreenstemmende bogronde (Tabel 2) is waarskynlik te wyte aan die hoer kleiinhoude daarvan (Tabell). Kleik6110lde is ook in staat om die afbraak van urease te inhibeer (Zantua, Dumenil & Bremner, 1977;Reynolds, Wolf & Armbruster, 1985). In die bogrondebestaan daar vir 'n periode van 10 tot 49 uur na toediening die gevaar dat ureum na di'e ondergronde sall60g (Tabel 2).…”
Section: Result~te En Bespreklngunclassified
“…This is con¢rmed by the results of Pettit et al [4], suggesting that the matrix-bound urease activity in soil may sometimes be up to 60% of the total activity. The potential urea ammoni¢cation rates (Table 3) showed an increasing level of activity from the setaside bulk soil to the barley bulk and rhizosphere soils (in this order), which could re£ect a general increase of organic content [5] or microbial biomass and activity [35]. However, the absence of correlation between potential ammoni¢cation rates (urease activity) and microbial urea turnover rates (P 6 0.2, Table 3) con¢rmed that the former gave no speci¢c or detailed information on microbial urea transformations in the soils, possibly because of a variable matrix-bound component.…”
Section: Soilmentioning
confidence: 87%
“…Dalal, (1975) reported that organic carbon and cation exchange capacity were positively correlated with urease activity in soils and also reported that urease activity was significantly correlated with oxalate extractable amorphous iron or aluminum, but not with pH and clay. Zantua et al, (1977) found that urease activity was significantly correlated with organic carbon, total nitrogen and CEC. Speir et al, (1980) found that urease activity was significantly correlated with total nitrogen, total sulphur, organic carbon and protease activity in soil, while Dash et al, (1981) reported a positive correlation between urease activity, total nitrogen, organic carbon, silt + clay and specific conductance and a negative correlation with pH and moisture.…”
Section: Fig1 Soil Enzyme Urease Activity In Various Samplesmentioning
confidence: 94%
“…Gould et al, (1973) andTabatabai, (1977) reported that in the soil profiles, the activity of urease enzyme decreased with depth. Zantua et al, (1977) reported that soil urease activity was largely influenced by the organic matter content, pH and specific soil area than any other soil properties and also reported that the soil urease activity is highly significant with total nitrogen.…”
Section: Fig1 Soil Enzyme Urease Activity In Various Samplesmentioning
confidence: 99%